Comparison of maximal anaerobic running tests on a treadmill and track - Nummela, A.; Hämäläinen, I.; Rusko, H. (Journal of Sports Sciences, 2007)
To develop a track version of the maximal anaerobic running test, 10 sprint runners and 12 distance runners performed the test on a treadmill and on a track. The treadmill test consisted of incremental 20-s runs with a 100-s recovery between the runs. On the track, 20-s runs were replaced by 150-m runs. To determine the blood lactate versus running velocity curve, fingertip blood samples were taken for analysis of blood lactate concentration at rest and after each run. For both the treadmill and track protocols, maximal running velocity (vmax), the velocities associated with blood lactate concentrations of 10 mmol · l-1 (v10 mM) and 5 mmol · l-1 (v5 mM), and the peak blood lactate concentration were determined. The results of both protocols were compared with the seasonal best 400-m runs for the sprint runners and seasonal best 1000-m time-trials for the distance runners. Maximal running velocity was significantly higher on the track (7.57 ± 0.79 m · s-1) than on the treadmill (7.13 ± 0.75 m · s-1), and sprint runners had significantly higher vmax, v10 mM, and peak blood lactate concentration than distance runners (P<0.05). The Pearson product - moment correlation coefficients between the variables for the track and treadmill protocols were 0.96 (vmax), 0.82 (v10 mM), 0.70 (v5 mM), and 0.78 (peak blood lactate concentration) (P<0.05). In sprint runners, the velocity of the seasonal best 400-m run correlated positively with vmax in the treadmill (r = 0.90, P<0.001) and track protocols (r = 0.92, P<0.001). In distance runners, a positive correlation was observed between the velocity of the 1000-m time-trial and vmax in the treadmill (r = 0.70, P<0.01) and track protocols (r = 0.63, P<0.05). It is apparent that the results from the track protocol are related to, and in agreement with, the results of the treadmill protocol. In conclusion, the track version of the maximal anaerobic running test is a valid means of measuring different determinants of sprint running performance.